Environmental and health & safety management a guide to compliance - Cheremisinoff, Nicholas P.; Graffia, Madelyn, 1962-; Knovel (Firm) (Park Ridge, N.J. : Noyes Publications, 1995)
This volume has been prepared for the Environmental and Health & Safety Manager. The EH & S manager is faced with the responsibility of handling both environmental policy/issues and occupational safety issues within organizations. Throughout the 1980s there was a proliferation of health and safety departments, environmental compliance personnel, and technical people associated with handling pollution control and waste management. American industry has been over the last several years contracting and downsizing their operations. In doing so, many corporations, large and small, are demanding greater responsibilities be delegated to middle and line function management. In this regard, many corporations are moving towards a single management entity, the EH & S manager, with responsibilities requiring extensive knowledge of both the environmental statutes and OSHA standards.
Originally published in print by Noyes in 1995.
Includes index.
Electronic reproduction.
Mode of Access: World Wide Web.
System requirements: Web browser and Adobe Acrobat Reader.
Keywords: Environmental law -- United States; Industrial safety -- Law and legislation -- United States; Industrial hygiene -- Law and legislation -- United States; Electronic books